Pengaruhdiameter Pelathelical Terhadap Dayadukung Tekan Pondasi Tianghelical Pada Tanah Gambut Dengan Metoda Pembebananconstant Stress Of Penetration - Unzi Marwan; Ferry Fatnanta; Soewignjo Agus Nugroho (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Foundation type selection is very influential on the building strength. One alternative of foundation type substitute for cerucuk is helical pile. Helical pile manufactured of steel consist of one or more helix-shaped bearing plates fixed to a central shaft that is rotated into the ground to support structure. This research presented the result of static loadingtest of helical pile on peat with constant stress penetration method. Datas of loading test in the form of load and penetration interpretation with Tangent of Intersection method and Terzaghi and Peck method. Pile variation in number and diameter of helix was conducted.Results indicate that addition of number helical will improve bearing capacity of helical pile. At pile that add with different helix's diameter, addition plate helical not affect significant to pile capacity for smaller diameter position on bottom. Comparison staticload test with empirical methods i.e method of Induvidual plate bearing and cylinder shear bearing. To sum up, cylinder shear bearing method more suite to static loading test than individual plate bearing method wiith standar error 0,79 and 1,79 respectivelly.Key words: helical pile, peat, individual plate bearing, cylinder shear